2014
DOI: 10.2478/s11532-013-0405-2
|View full text |Cite
|
Sign up to set email alerts
|

Controlled pesticide release from biodegradable polymers

Abstract: Polymers have been widely used in agriculture for applications including controlled release of pesticides and other active ingredients. The ability to predict their delivery helps avoid environmental hazards. Macromolecular matrices used as carriers in controlled release of agricultural active agents, especially pesticides, are reviewed. The review focuses on the advantages and mechanisms of controlled release. It includes biodegradable polymers in agriculture, their manufacturing methods, and their degradatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
169
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(171 citation statements)
references
References 141 publications
2
169
0
Order By: Relevance
“…These results qualify the polymers used, since one of the criteria for the materials used as seed coat film is that they do not react negatively with the chemicals and do not affect the physiological quality (ROY et al, 2014), thereby corroborating the results found by Castañeda et al (2014), Keawkham et al (2014) and Melo et al (2015), where no changes were observed in the physiological potential of rice seeds and other agricultural species when they were treated with phytosanitary and polymer coatings. For soybean seeds, Verma and Verma (2014) considered the benefits of the association and compatibility of the polymer material with the fungicide, resulting in higher percentages of germination.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…These results qualify the polymers used, since one of the criteria for the materials used as seed coat film is that they do not react negatively with the chemicals and do not affect the physiological quality (ROY et al, 2014), thereby corroborating the results found by Castañeda et al (2014), Keawkham et al (2014) and Melo et al (2015), where no changes were observed in the physiological potential of rice seeds and other agricultural species when they were treated with phytosanitary and polymer coatings. For soybean seeds, Verma and Verma (2014) considered the benefits of the association and compatibility of the polymer material with the fungicide, resulting in higher percentages of germination.…”
Section: Resultssupporting
confidence: 79%
“…The ability of thiamethoxam to bind to the mineral particles of clay and organic matter through sorption is greater in clayey soils as compared to more sandy soils. Leaching is prevented to a greater extent by the presence of more organic matter (BROZNIĆ et al, 2012;ROY et al, 2014). Avelar et al (2012) observed that maize seeds coated with the PolySeed CF polymer had five times more efficiency in the retention of Furazin 310 TS® insecticide containing 210 g zinc L -1 , used for the treatment of seeds.…”
Section: Resultsmentioning
confidence: 99%
“…R apid biodegradation of plant-derived substances is advantageous because it leads to less environmental contamination, although it also has disadvantages because it reduces residual activity and creates the need for repeated application of the product (35) (37) (38) (39) (40) . Placing the substance in a CRD may therefore increase the duration of residual activity and protect against degradation (41) .…”
Section: Discussionmentioning
confidence: 99%
“…These formulations, besides providing the slow-release profile to the pesticide, also increase the water-holding capacity of soil (Roy et al 2014). After their degradation, these are helpful as compost in the field (Kumar et al 2014).…”
Section: Controlled-release Agrochemical Delivery Systems and Their Amentioning
confidence: 99%
“…Due to the direct influence of swelling on the release found for these polymer matrices. The adjustment of the swelling behavior by formulating mixtures with other polymers proves to be an interesting tactic to modify the release of the fertilizer (Roy et al 2014;Zhang et al 2014a). In case of fertilizer chemicals, hydrogels are capable of storing large amounts of fertilizer, gradually releasing it into the soil, retaining the fertilizers concentration longer and in optimal conditions.…”
Section: +3mentioning
confidence: 99%